2014
DOI: 10.3109/14992027.2014.887230
|View full text |Cite
|
Sign up to set email alerts
|

WFS1 mutations in hearing-impaired children

Abstract: WFS1 gene mutations are a rare cause of HI among Finnish children with HI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…The rare homozygous variant, p. Gly674Arg, in the WFS1 gene was observed in an individual with Arab ethnicity who was apparently normal (unlikely to be related to Wolfram syndrome). The variant is considered to be pathogenic/likely pathogenic (Khanim, Kirk, Latif, & Barrett, ) but our data support the idea that this variant is polymorphism in the homozygous state and it can be considered to be causative only when occurring in trans with other variants in the WFS1 gene (Häkli, Kytövuori, Luotonen, Sorri, & Majamaa, ). This variant should also be reclassified as of uncertain significance in its homozygous state.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The rare homozygous variant, p. Gly674Arg, in the WFS1 gene was observed in an individual with Arab ethnicity who was apparently normal (unlikely to be related to Wolfram syndrome). The variant is considered to be pathogenic/likely pathogenic (Khanim, Kirk, Latif, & Barrett, ) but our data support the idea that this variant is polymorphism in the homozygous state and it can be considered to be causative only when occurring in trans with other variants in the WFS1 gene (Häkli, Kytövuori, Luotonen, Sorri, & Majamaa, ). This variant should also be reclassified as of uncertain significance in its homozygous state.…”
Section: Resultssupporting
confidence: 63%
“…normal (unlikely to be related to Wolfram syndrome). The variant is considered to be pathogenic/likely pathogenic (Khanim, Kirk, Latif, & Barrett, 2001) but our data support the idea that this variant is polymorphism in the homozygous state and it can be considered to be causative only when occurring in trans with other variants in the WFS1 gene (Häkli, Kytövuori, Luotonen, Sorri, & Majamaa, 2014).…”
supporting
confidence: 66%
“…The family history, clinical, and biochemical features of the six patients who were identified as positive after NGS for a variant of uncertain significance (VUS), likely pathogenic or pathogenic, were reported. A summary is presented in Table 1 [ 15 , 16 , 17 , 18 , 19 , 20 ]. Six other patients showed benign or likely benign variants after NGS analysis, and sixteen showed a negative result.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, two additional heterozygous mutations have also previously been reported in a de novo state. One WFS1 pathogenic variant p.G831S (c.2492G>A) was found in a Finland sporadic case with NSHL and another p.H313Y (c.937C>T) mutation was shared by two unrelated Danish sporadic patients with WLS (Hakli, Kytovuori, Luotonen, Sorri, & Majamaa, 2014; Hansen et al., 2005). To our knowledge, together with our present study, there are only four de novo mutations in WFS1 reported in different racial backgrounds from Asian, European, and US/Caucasian ancestries (Table 1).…”
Section: Discussionmentioning
confidence: 99%